Subcellular localization- and fibre type-dependent utilization of muscle glycogen during heavy resistance exercise in elite power and Olympic weightlifters - Hokken, R.; Laugesen, S.; Aagaard, P.; Suetta, C.; Frandsen, U.; Ørtenblad, N.; Nielsen, J. (Acta Physiologica, 2020)
Aim Glycogen particles are found in different subcellular localizations, which are utilized heterogeneously in different fibre types during endurance exercise. Although resistance exercise typically involves only a moderate use of mixed muscle glycogen, the hypothesis of the present study was that high-volume heavy-load resistance exercise would mediate a pattern of substantial glycogen depletion in specific subcellular localizations and fibre types.